THE INFLUENCE OF TIME LOADING AND UNLOADING ON FUNCTIONINGST COMPLEXS OF SMALL AUTOTRANSPORT SYSTEMS CARGO TRANSPORTATION BY TRANSPORT OF COMMON USE - E. S. Fedoseenkova; E. E. Vitvitskiy (Вестник СибАДИ)
The influence of the idle time during loading and unloading on the results of the work of a group of vehicles in the aggregate of small motor transportation systems of cargo transportation was investigated. The solution of the problem is represented by the example of brick transport on pallets from the manufacturing plant in the city by rolling stock of general use. The dependencies of the results of the work of a group of vehicles in the aggregate of small motor transport systems have been established, and their verification has been carried out for adequacy of the process under influence.